Mortality and causes of death: a comparative study between indigenous and non-indigenous areas in Costa Rica - Fantin, Romain (2022)
Introduction. In most countries of the American and Oceanic continents, indigenous people have worse health indicators than the rest of the population. The objective of this study is to analyze the differences in mortality and causes of death between people living in indigenous areas, and people living in the rest of Costa Rica, between 2010 and 2018. Methodology. The study population is based on the 2010 National Electoral Rolls. The Registry of the National Institute of Statistics and Censuses (INEC) allowed knowing the cause of death (ICD-10). 2,747,616 people for 23,985,602 person-years of follow-up were included. Results. No differences in mortality in men were observed between both populations. In women, mortality was slightly higher in indigenous areas. In indigenous areas, mortality was higher in people who were under 50 years of age at the beginning of the follow-up, compared to the rest of the population, in particular mortality due to Diseases of the digestive system and External causes of morbidity and mortality. Mortality was lower in indigenous areas in people over 70 years of age, particularly mortality due to Tumors and Diseases of the circulatory system. Conclusions. The results of this study do not confirm the hypothesis of systematically higher mortality in populations living in indigenous areas.